Проєктування гідроприводу підземного модуля для збирання та зберігання твердих побутових відходів - Козлов, Леонід Геннадійович; Піонткевич, Олег Володимирович; Костенко, Євген Олександрович; Мазурін, Василь Васильович; Kozlov, Leonid; Piontkevych, Oleh; Kostenko, Yevhen; Mazurin, Vasyl (Запоріжжя : Видавничий дім «Гельветика», 2025)
UA: Закрите збирання та зберігання твердих побутових відходів в громадських і комерційних зонах вирішено шляхом проєктування підземного модуля на основі гідроприводу. Розглянуто конструктивні особливості підземних модулів різних виробників. Проведено аналіз гідроприводів для синхронізації руху його гідроциліндрів. Запропоновано конструкцію підземного модуля для збирання та зберігання твердих побутових відходів на основі гідроприводу з механічним стабілізатором. Розроблено схему гідроприводу підземного модуля на основі гальмівного клапана для забезпечення постійної швидкості опускання його платформи. Проведено проєктний розрахунок для вибору основних комплектуючих гідроприводу. Проведено інженерний аналіз гідроциліндрів гідроприводу. Отримані результати будуть корисні інженерам і виробникам при проєктуванні гідроприводів підземних модулів для збирання та зберігання твердих побутових відходів. /// EN: The issue of closed collection and storage of solid household waste in public and commercial areas has been addressed through the design of a hydraulically driven underground module. The design features of underground modules from various manufacturers, which provide high-quality and competitive products for solid household waste collection and storage, are reviewed. An analysis of hydraulic drives regarding the synchronization of hydraulic cylinder movement was conducted. Current solutions for synchronizing hydraulic cylinders based on throttle control, pressure-compensated flow control valves, and flow dividers/combiners are highlighted. A design for an underground solid household waste collection and storage module based on a hydraulic drive with a mechanical stabilizer, which increases the rigidity of the synchronizing system, is proposed. A hydraulic drive circuit for the underground module has been developed based on a counterbalance valve to ensure a constant lowering speed of the platform. A counterbalance valve with mixed pilot control was selected, which prevents cavitation processes in the hydraulic drive, ensures energy savings during platform lowering, and hermetically holds the loaded hydraulic cylinders, preventing them from drifting. Design calculations were performed to select the main hydraulic components: hydraulic cylinders, a gear pump, and a hydraulic tank. A 4/3-way normally closed solenoid-operated directional control valve was chosen as the fluid flow regulator to ensure automated control of the underground module's operation. An engineering analysis of the hydraulic cylinders was conducted to ensure reliability. Engineering calculations were performed using the SOLIDWORKS Simulation module. The most stressed parts of the hydraulic cylinder under load were identified. The impact of the load on deformation and stress for different hydraulic cylinder designs was calculated. Additionally, a comparison of the load's impact on the safety factor was conducted to select the hydraulic cylinder configuration. The obtained results will be useful to engineers and manufacturers when designing hydraulic drives for underground solid household waste collection and storage modules.
Design of the Hydraulic Drive for an Underground Solid Household Waste Collection and Storage Module
Keywords: підземний модуль; гідроапаратура гідроприводу; гальмівний клапан; інженерний аналіз; underground module; hydraulic drive components; counterbalance valve; engineering analysis